A convex hull‐based approach for multiaxial high‐cycle fatigue criteria. Issue 1 (9th August 2020) - Scalet, Giulia
Abstract: Design methods against multiaxial high‐cycle fatigue require the formulation of appropriate criteria that differ in the definition of critical measures introduced to quantify damage, as the amplitude of shear stress. The present paper proposes a novel approach to compute the amplitude of shear stress in multiaxial high‐cycle fatigue. The approach is based on the computation of the convex hull enclosing the stress history under investigation and is validated on proportional and non‐proportional paths in several dimensions and for different materials. High accuracy is achieved when compared with alternative methods from the literature.